Expression of preoperative KISS1 gene in tumor tissue with epithelial ovarian cancer and its prognostic value. Issue 46 (November 2016) - Cao, Fang; Chen, Liping; Liu, Manhua; Lin, Weiwei; Ji, Jinlong; You, Jun; Qiao, Fenghai; Liu, Hongbin
Abstract : Abstract: Our study aimed to elucidate the role of Kisspeptin (KISS1) in tumor tissues of patients with epithelial ovarian cancer (EOC) and investigate the prognostic value of this biomarker. Forty EOC patients and 20 uterine fibroids female patients with healthy ovaries undergoing cytoreductive surgery between January 2010 and January 2014 in our hospital were enrolled in this study. KISS1 expression in tumor and normal tissues was detected. Correlations between clinic-pathologic variables and KISS1 expression in EOC tissues and the prognostic value of KISS1 for overall survival were evaluated. During the follow-up of 11.2 to 62.1 months, the overall survival rate and mean survival time were 28.9% (11/38) and 38.35 ± 2.84 months. Preoperative KISS1 mRNA was higher in tumor tissue than in normal tissue ( P  <0.001), and it was associated with histologic grade of tumor, surgical FIGO stage, metastasis, and residual tumor size (all P  <0.05). Multivariate survival analysis indicated significant influence of residual tumor size (HR = 2.357, P  = 0.039) and preoperative KISS1 mRNA (HR = 0.0001, P  <0.001) on mean survival time. Patients with low KISS1 mRNA expression had shorter survival time than those with high expression ( P  = 0.001). Preoperative KISS1 mRNA was a potential prognostic biomarker for EOC, and high preoperative KISS1 expression indicated a favorable prognosis.